Design of Balance Control System for Quadcopter Drone Using Ziegler-Nichols PID Method - Widiyanto, Sinung; Taufiqurrohman, Muhammad; Suhirwan, Suhirwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Unmanned Aerial Vehicles (UAVs) are currently experiencing rapid development for both general and military applications. Among the various types of UAVs, the quadcopter stands out as a multirotor aircraft capable of vertical take-off and landing (VTOL). The primary factors affecting the imbalance of a quadcopter typically include payload weight and wind disturbances. The payload carried by the quadcopter can lead to instability during flight, while wind, as an external factor, significantly affects the aircraft’s stability. Irregular wind direction and speed can shake the quadcopter's body, resulting in unstable flight conditions. Developing a quadcopter that remains stable during flight, selecting an appropriate control method is crucial to achieve the desired balance. One effective approach for controlling brushless motor speed is the Proportional-Integral-Derivative (PID) control method. Among various PID tuning methods, the Ziegler-Nichols method is considered effective for this application.Based on this study, the control of the roll (ɸ) and pitch (θ) angles of the quadcopter yielded the following PID parameters: Kp = 15, Ki = 0.55, and Kd = 0.13. The results indicate that the quadcopter has not yet achieved perfect stability in flight. This research represents an initial stage in designing a quadcopter balance control system using the Ziegler-Nichols PID tuning method.